Autonomous learning patterns of students with special needs in quantum learning using flipbook media at Indonesia - Rohmah, Ima Isnaini Taufiqur; Nurdianingsih, Fitri; Rahmawati, Okta Ika; Prasetyo, Achmad Danny; Asyidda, Rossdina (Edelweiss Applied Science and Technology, 2024)
Autonomous learning referred to students’ ways and processes to develop their learning skill independently and take responsibility of it. Autonomous learning encouraged students to have active responsibility in their learning process, develop their metacognitive skill, and be more independent and proactive learners. This study aimed to investigate autonomous learning pattern of students with special needs in quantum learning using flipbook media. This was qualitative research in form of case study. The participants were primary school students at Bojonegoro Regency, Tuban Regency, and Cepu Regency. Those regencies covered various students’ backgrounds and special needs. From all participants, five students were selected specifically. They were selected because they showed characteristics of autonomous learning skill that could be easily identified. Data was collected using observation and in-depth interview. Technique in analyzing data was thematic analysis technique. Data was validated using member checking. Result of study showed that students with special needs who utilized flipbook media in quantum learning tend to be more independent in setting learning goals, managing learning process, taking initiative, completing assignments, and conducting self-reflection to their progress. It could be concluded that quantum learning using flipbook media could be effectively create five patterns of autonomous learning for students with special needs at Indonesia.